Chipping Away at Workplace Privacy: The Implantation of RFID Microchips and Erosion of Employee Privacy - Wes Turner (Washington University Journal of Law & Policy, 2020)
With the advent of new technologies and workplace policies, employees have lowered expectations of privacy. These technologies and policies include the implantation of microchips in employees; bring your own device to work policies; and wearable technologies. The lack of both state and federal statutes to protect employees means that employees have few methods to redress their privacy concerns. To protect their privacy rights, employees should use a collectivist approach to bargain with their employers for such rights.
Keywords: RFID; worker' s rights; employee privacy; privacy; workplace surveillance